2009
DOI: 10.1080/02770900802460514
|View full text |Cite
|
Sign up to set email alerts
|

Are Genes Associated with Energy Metabolism Important in Asthma and BMI?

Abstract: Polymorphisms of the leptin gene may be associated with asthma and higher BMI in asthmatic patients. Polymorphisms of the LEPR and GHRL seem unlikely to be associated with asthma or BMI in our sample. The results of haplotype analysis for the LEPR gene may suggest a protective role of the GG haplotype against asthma; however, studies on larger groups are necessary to confirm the observed trend towards association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
1
18
2
1
Order By: Relevance
“…BMI, body mass index; OR, odds ratio; CI, confidence interval. molecules leptin and tumor necrosis factor alpha (TNFα) as well as the ubiquitously expressed protein kinase C alpha, a factor associated with adipocyte differentiation and insulin signaling (7,22,23). Cell cycle control genes have so far not been investigated in this respect, but their importance in inflammatory processes confer them etiologic plausibility to potentially modify the obesity-asthma relationship.…”
Section: Asthma In Obese Peoplementioning
confidence: 99%
“…BMI, body mass index; OR, odds ratio; CI, confidence interval. molecules leptin and tumor necrosis factor alpha (TNFα) as well as the ubiquitously expressed protein kinase C alpha, a factor associated with adipocyte differentiation and insulin signaling (7,22,23). Cell cycle control genes have so far not been investigated in this respect, but their importance in inflammatory processes confer them etiologic plausibility to potentially modify the obesity-asthma relationship.…”
Section: Asthma In Obese Peoplementioning
confidence: 99%
“…12 PRKCA, LEP, and TNFa were studied in individual surveys and the results were promising. 8,9,11 Why the ADRB2 polymorphism seems to be worth studying in the context of asthma and obesity phenotype? The same defect, which leads to a poorer response to the bronchodilator treatment, could be responsible for inadequate lipolysis and energy storage thus affecting both conditions.…”
Section: Shared Genetic Factors For Asthma and Obesitymentioning
confidence: 99%
“…7 Between commonly shared genes, the most biologicaly plausible are those that are pleiotropic, including b2-adrenergic receptor (ADRB2), vitamin D receptor gene (VDR), leptin (LEP), protein kinase C alpha (PRKCA), and tumor necrosis factor a (TNFa). [8][9][10][11][12] Polymorphisms within ADRB2 were described in association with different disorders, including not only asthma and obesity but also hypertension, 13 autism, 14 cerebral palsy, 15 susceptibility to parasite infestation, 16 and rheumatoid arthritis. 17 The ADRB2 Gene…”
mentioning
confidence: 99%
“…A pediatric case-control study has shown a significant association between polymorphisms in the leptin gene and asthma, although there were no associations with polymorphisms in the leptin receptor or ghrelin gene [35]. In familybased association studies involving parent-child trios in both a Costa Rican cohort, and the Childhood Asthma Management Program cohort, single-nucleotide polymorphisms (SNPs) of the PRKCA gene (protein kinase C alpha) were associated with both BMI and asthma [36 ].…”
Section: Shared Genetic Determinants In Obesity and Asthmamentioning
confidence: 99%